A Design of Antipodal Vivaldi Antenna with Circular Load for Bandwidth Enhancement in Radar Applications - Galuh Widya Cahyaningtyas; Fannush Shofi Akbar; Risdilah Mimma Untsa; Puguh Chondro Jadmiko; Efrilia M. Khusna; Djoko Kuntjoro, Tri Agus (Journal of Computer, Electronic, and Telecommunication (COMPLETE), 2024)
Radio Detection and Ranging (RADAR) attracts a lot of attention because it has an important role in life through its various applications such as in security, navigation, transportation, telecommunications and medical applications. Ultra-wideband radar applications require accurate, high-resolution detection and good penetration capabilities. To fulfil this, the bandwidth required must be greater, resulting in a narrower pulse width. In this case, an antenna using ultra-wideband technology is needed to accommodate this. This research discusses the design of an ultra-wideband antipodal vivaldi antenna with the addition of circular loads designed to increase bandwidth in radar applications. The design and simulation in this study used CST Studio Suite 2019 software and then measured with a Vector Network Analyzer (VNA) to determine antenna performance. The results of this study show that the antenna can work at a frequency of 898.85 MHz to more than 3.2 GHz with a unidirectional radiation pattern. In addition, the gain generated in this study is 6.6 dBi, S1.1 -17.01 dB, and a bandwidth of more than 2301.15 MHz.